Acquisition of Iron by Alkaliphilic Bacillus Species - McMillan, Duncan G. G. (American Society for Microbiology (ASM), 2010)
The biochemical and molecular mechanisms used by alkaliphilic bacteria to acquire iron are unknown. We demonstrate that alkaliphilic (pH > 9) Bacillus species are sensitive to artificial iron (Fe(3+)) chelators and produce iron-chelating molecules. These alkaliphilic siderophores contain catechol and hydroxamate moieties, and their synthesis is stimulated by manganese(II) salts and suppressed by FeCl(3) addition. Purification and mass spectrometric characterization of the siderophore produced by Caldalkalibacillus thermarum failed to identify any matches to previously observed fragmentation spectra of known siderophores, suggesting a novel structure.